The Effect of a Self-Management and Social Support Program on New Hypertension Cases with Uncontrolled Blood Pressure - อินทบุตร คณิตตา (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2020)
This quasi-experimental research aimed to study the effectiveness of self-management with social support programs in new cases of hypertension who have uncontrolled blood pressure levels. The patient must be diagnosed with hypertension. The blood pressure (BP) have more than or equal to 140/90 mmHg for the last 2 times. The patients have registered as a hypertension for not more than 6 months, but must be having not a history of hypertension from elsewhere. The sample of this study was hypertension patients aged 18-60 years receiving services at the out-patient department of U-Thong Hospital, Suphanburi. The 60 samples were randomly divided into the experimental group (n=30) and the comparison group (n=30). The study took a total of 9 weeks. The experimental group was provided with the self-management and social support programs consisted of problem solving. The activity was arranged 3 times in 1.5 hour sessions each at the hypertension clinic, U-Thong hospital according to appointment system of the hospital. After the third activities, 5 minutes telephone follow-up was used by the researcher to encouraged self-management behavior. Post-test was conduct at the 1st week and 3rd weeks after intervention. The comparison group received brochures about hypertension and routine health education by health care providers. The data were collected by using questionnaires during the pre-post experiment and follow-up stage, and was analyzed using descriptive statistics chi-square, repeated measure ANOVA, and independent t-test. The results found that, the experimental group had significantly better mean scores of self-management behavior to control blood pressure levels and blood pressure levels (BP) better than pre-experiment and comparison group (p-value <0.05). It is suggested that the selfmanagement and social support programs used with change of behavioral in self-management to control blood pressure. It also uses the social support to help control the blood pressure levels of patients as well. Highlight of the program is to have an appointment consistency with the hospital appointment system. Patients are tracked through with network partners which the patients to participate in the activities as scheduled and receive the complete program. That could be used with hypertensions new case to enhance their selfmanagement skills affecting the blood pressure levels.